Pattern Recognition in Bioinformatics - Chetty, Madhu (Springer, 2017)
This book constitutes the refereed proceedings of the International Workshop on Pattern Recognition in Bioinformatics, PRIB 2008, held in Melbourne, Australia, in October 2008.